Intelligence Quetiont (IQ), Emotional Quetiont (EQ), dan Spiritual Quetiont (SQ) Qur`ani Ulul Albab - Adha Saputra; Iwan Satiri; Lira Erlina (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD Cianjur, 2021)
A misguided understanding of Western intellectuals rationalism and emperism in modernization so that it turns into westernization is a phenomenon that is a problem of today's society. The negative impact that arises from this phenomenon is the crisis of spirituality of modern society. This fact led to the importance of grounding the concepts of IQ, EQ, and SQ Qur'ani ulul albab as preventive solutions. The importance of the concepts of IQ, EQ, and SQ Qur'ani ulul albab, because all abilities arising from ulul albab can selectively integrate rationality and spirituality by operationalizing dhikr and thinking activities.